MEMBUAT ANIMASI STANDARD OPERATION PROSEDUR (SOP) PELAYANAN PERIZINAN BERBASIS OSSRBA PADA DINAS PERIZINAN OKU MENGGUNAKAN ODOBE FLASH CS6 - Anuar, Saipul; Rusidi, Rusidi; Meilantika , Dian (JIK : Jurnal Informatika dan Komputer, 2024)
Moving images in the from of a set of objects arranged in an orderly manner following a predetermined movement at each increment at each increment of time that occurs. Bisness license granted to business actors to start and run their business actors to start and run their business activities which are assessed based on the level of risk of business. Adobe flash cs6 is on of the superior product of adobe system. Adobe flash cs6 is user to create vector images and animated images. .Keywords:Animation, micro small and medium enterprises, adobe flash cs6